Recurrent infectious subcapsular renal hematoma accompanied by microaneurysm - Ozeki, Toshikazu (CEN Case Rep, 2018)
An 80-year-old woman was admitted to the hospital complaining of loss of appetite. 10 days earlier, her oral intake gradually decreased with no other specific symptoms, such as abdominal pain, nausea, vomiting, headache, or low back pain. Abdominal computed tomography (CT) scan revealed a left subcapsular renal hematoma. We suspected infective subcapsular renal hematoma, so percutaneous needle aspiration and drainage were performed. Intravenous sulbactam–ampicillin was started immediately. On day 9 after admission, repeat CT scan revealed the subcapsular hematoma had reduced in size. The drain was removed, and intravenous antibiotics were discontinued. Follow-up CT scan on day 21 revealed increased subcapsular renal hematoma size. The patient also had high fever. Suspecting recurrence of infective subcapsular renal hematoma, we repeated the drainage of the hematoma and restarted intravenous antibiotics. Renal arteriography showed a renal artery microaneurysm and her condition improved with renal artery embolization. Renal arteriography was useful for detecting renal artery microaneurysm in infective subcapsular renal hematoma that did not resolve after antibiotic treatment and drainage.